Mary Elizabeth Braddon’s Thou Art the Man (1894): Scoundrel Fathers, Fugue States, and the Problematized Real in Victorian Sensation Novels - Susan S., Nash, (IJRDO - Journal of Social Science and Humanities Research, 2018)
Mary Elizabeth Braddon (1837-1915) is known for her sensation novels – novels written for all levels of readers, those grabbing a cheap book bound in yellow covers and sold in railway stations, and those serialized in popular magazines (one of which she founded and ran). They explored the dark sides and inner workings of Victorians at all levels: prim and proper professionals, landed gentry, impoverished women, people in desperate poverty, and they explore secrets and the question: “What on earth do you do if you find yourself in an impossible situation?” I often wonder what kind of father Mary Elizabeth Braddon had. Her books are chock-full of absolutely amoral (if not immoral) fathers, who are frauds, imposters, scam artists, wastrels, cheats, bigamists, and, in some cases sociopathic murderers.